Decreasing acid value of fatty acid ethyl ester products using complex enzymes - Li, Yuting; Guo, Jingjing; Sun, Shangde (Frontiers in Bioengineering and Biotechnology, 2024)
Recently, enzymatic method has been used to prepare biodiesel using various oils. But the high acid value of the biodiesel product using enzyme as a catalyst has been one issue. In this work, an attempt to reduce the acid value of fatty acid ethyl ester (FAEE) product to satisfy the specified requirement (AV ≤ 0.5 mgKOH/g), a complex enzyme-catalyzed method was used for the ethanolysis of Semen Abutili seed oil (SASO) (AV = 5.5 ± 0.3 mgKOH/g). The effects of various variables (constituents of complex enzyme, type and addition of water removal agent, time, temperature, enzyme addition load, substrate ratio) on the enzymatic reaction were investigated. The optimal reaction conditions were: 1% addition of liquid lipase Eversa® Transform 2.0% and 0.8% of enzyme dry powder CALB, reaction temperature 35°C, alcohol-oil ratio 9:1 (mol/mol), 0.8 g/g of 4A-MS and reaction time 24 h. Under the optimal reaction conditions, the FAEE yield was 90.8% ± 1.5% and its acid value was decreased from 12.0 ± 0.2 mgKOH/g to 0.39 ± 0.10 mgKOH/g. In further evaluating the feasibility of preparing FAEE from SASO, the FAEE products obtained under the optimal reaction conditions were purified and evaluated with reference to the ASTM D6751 standard for the main physicochemical indexes. The results obtained were in accordance with the requirements except for the oxidative stability.